Leak closure following left atrial appendage exclusion procedures: A multicenter registry. Issue 6 (1st March 2022) - Killu, Ammar M.; Gbolabo Adeola, Oluwaseun; Della Rocca, Domenico G.; Ellis, Christopher; Sugrue, Alan M.; Simard, Trevor; Friedman, Paul A.; Kawsara, Akram; Horton, Rodney P.; Natale, Andrea; Alkhouli, Mohamad; Holmes, David R.
Abstract: Background: Though infrequent, incomplete left atrial appendage closure (LAAC) may result from residual leaks. Percutaneous closure has been described though data is limited. Methods: We compiled a registry from four centers of patients undergoing percutaneous closure of residual leaks following LAAC via surgical means or with the Watchman device. Leak severity was classified as none (no leak), mild (1–2 mm), moderate (3–4 mm), or severe (≥5 mm). Procedural and clinical success was defined as the elimination of leak or mild residual leak at the conclusion of the procedure or follow‐up, respectively. Results: Of 72 (age 72.2 ± 9.2 years; 67% male) patients, 53 had undergone prior LAAC using the Watchman device and 19 patients surgical LAAC. Mean CHADS2 ‐VA2 Sc score was 4.0 ± 1.8. The median leak size was 5 mm, range: 2–13). A total of 13 received Amplatzer Vascular Plug‐II, 18 received Amplatzer Duct Occluder‐II and 40 patients received coils. One underwent closure using a 21 mm‐Watchman. Procedural success was 94%. Zero surgical and nine Watchman patients (13%) had a residual leak at procedural‐end (five mild, three moderate, and one severe)—only one patient had no reduction in leak size. Overall leak size reduction was 94%. Two (3%) had intraoperative pericardial effusion. There were no device embolizations, device‐related thrombi, or procedural deaths. Clinical success was maintained at 94%. Two had cerebrovascular accidents—at 2 days (transient ischemic attack) and 10 months postprocedure. Two had major bleeding outside the 30‐day periprocedural window. Conclusion: Percutaneous closure of residual leaks following left atrial appendage closure is feasible and associated with good outcomes. The procedural risk appears to be satisfactory.